CLAIMS IN INTERNATIONAL CONSTRUCTION PROJECTS IN ETHIOPIA and CASE STUDIES ON SELECTED PROJECTS - Dinku, Abebe; Kahssay, Girmay (Zede Journal of Ethiopian Engineers and Architects, 2023)
With the advent of the liberalization of the economy and availability of funds from international financers, there has been a surge of large-scale civil engineering construction in Ethiopian construction industry. While this large scale investment in the construction sector has been a major step in the right direction, this venture has been beset with unfortunate incidences of claims ranging in millions of Birr and sometimes even in excess of 100% of the project costs. Claims are demands for money and/or time extension that a contractor rightly or wrongly believes he has a right to. Whilst claims are an inevitable fact in the construction industry, future handling of such incidents will have to depend on developing a healthy understanding of their occurrences and fonnulating .a strategy of minimizing risks associated with it. The objectives of this paper are, therefore, to investigate the causes of potential claims and to propose a possible mitigation as to the handling of similar incidents in the future. In addition to literature survey, questionnaires based studies were made to identify thE!causes of claims in Ethiopian construction sector and interviews were also conducted with various parties of the sector. The paper attempts also to analyze case studies and points out remedial measures, to reduce their impact. One of the main observations of this research work has been the fact that the Ethiopian construction industry seriously lack qualified engineering professionals with an appropriate level of training in construction management, international contract administration and claims handling. Finally the findings of the study are discussed and recommendations forwarded